The missing link: Rhyncogonus Sharp in the Gambier Islands (Coleoptera, Curculionidae, Entiminae, Rhyncogonini) - Ramage, Thibault (Zootaxa, 2021)
The genus Rhyncogonus Sharp, 1885, is represented in French Polynesia by 65 species found in the Austral, Marquesas, Society and Tuamotu archipelagos. Hitherto unknown from the fifth archipelago of French Polynesia, the Gambier Islands, a new species of Rhyncogonus has been discovered by the botanist Jean-François Butaud on Motu Teiku, a small island never previously investigated for plants and insects. Rhyncogonus duhameli sp. nov. is here described and illustrated.